Targeting ferroptosis in spinal cord injury through stem cell therapy: mechanisms and therapeutic prospects - Qiqin Shen; Lingdi Wu; Chuyi Cai; Bingbing Li; Fang Yu (Frontiers in Neuroscience, 2025)
Spinal cord injury (SCI) is a traumatic neurological disorder with a high incidence and limited clinical treatment options. Ferroptosis, a newly discovered form of programmed cell death, has shown significant research potential in the field of neurological diseases. Stem cells have become an ideal therapeutic option for various diseases due to their multidirectional differentiation potential and paracrine properties. Existing studies have demonstrated that stem cells possess substantial potential in the repair of spinal cord injuries. Recent research has found that stem cell transplantation can improve the pathological process of SCI by regulating the ferroptosis pathway. This review systematically described the molecular mechanisms of ferroptosis in SCI, the biological effects of stem cell therapy for SCI, and the therapeutic potential of stem cell-targeted regulation of ferroptosis. Additionally, we proposed three key research directions: cross-study of ferroptosis signaling pathways and stem cell action mechanisms, optimization strategies for therapeutic stem cells, and multimodal combined treatments based on ferroptosis regulation. This review aimed to provide new theoretical foundations and research perspectives for stem cell therapy in SCI.